RELATIONSHIP BETWEEN FAMILY SUPPORT AND ANXIETY LEVEL CLIENTS OF CORONARY HEART DISEASE (CHD) AT THE HEART POLYCLINIC OF RSUD IN LANGSA - Hartati, Irma; Fitriyani, Fitriyani (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2022)
Background: Cardiovascular disease is the worlds number one cause of death. Family support can help improve individual coping mechanisms by providing emotional support and suggestions on alternative strategies based on previous experience. Anxiety is an uneasy feeling that is vague due to discomfort or fear that is accompanied by a response (the cause is not specific or unknown to the individual). Purpose: To determine the relationship between family support and the level of anxiety in coronary heart disease clients. Methods: This study uses analytic methods with the design cross sectional approach. The sampling technique uses Accidental sampling technique. Result: There is a relationship between family support and the level of anxiety in coronary heart disease clients with p-value 0.033 (p0.05). Conclusion: The result of this study found that there was a relationship between family support and anxiety level in coronary heart disease clients at the Heart Polyclini at RSUD (Regional Public Hospital) Langsa.